Loss of nectin‐3 expression as a marker of tumor aggressiveness in pancreatic neuroendocrine tumor. Issue 2 (19th December 2019) - Hirabayashi, Kenichi; Tajiri, Takuma; Bosch, Dustin E.; Morimachi, Masashi; Miyaoka, Masashi; Inomoto, Chie; Nakamura, Naoya; Yeh, Matthew M.
Abstract : Pancreatic neuroendocrine tumors (PanNETs) are rare, and prediction of aggressive characteristics, such as recurrence and metastasis and prognosis of PanNETs remain difficult. Nectins are cell adhesion molecules that regulate the formation of adherens and tight junctions. In this study, we investigated the clinicopathological significance of nectin‐3 expression in patients with PanNETs. Immunohistochemical analysis of nectin‐3 expression was performed on 78 cases of PanNET. Low nectin‐3 expression in the membrane (positive ratio ≤25%) was observed in 62 cases (79.5%) and was significantly correlated with larger tumor size (>20 mm; P = 0.003), G2/G3 tumors ( P = 0.025), higher Ki67 labeling index (≥3%; P = 0.009), lymphatic involvement ( P = 0.047), advanced pT‐factor (T2–T4; P = 0.003), lymph node metastasis ( P = 0.006), advanced Union for International Cancer Control/American Joint Committee on Cancer‐stage (Stage II–IV; P = 0.001), advanced ENETS stage (Stage IIa–IV; P = 0.001), nonfunctioning tumors ( P = 0.002), and a shorter disease‐free survival ( P = 0.019). However, there was no significant correlation between nectin‐3 expression in the membrane and/or cytoplasm and the clinicopathological parameters. The present results suggest that decreased nectin‐3 expression in the membrane is associated with increased tumor aggressiveness of PanNETs. Clinically, immunohistochemical analysis of nectin‐3 may help predict tumor aggressiveness for PanNETs.